A unique patterned diamond stamp for a periodically hierarchical nanoarray structure. (23rd September 2016) - Wang, Yi; Shen, Yanting; Xu, Weiqing; Xu, Shuping; Li, Hongdong
Abstract: A diamond stamp with a hierarchical pattern was designed for the direct preparation of a periodic nanoarray structure, which was prepared by the reactive ion etching technique with a hierarchical ultrathin alumina membrane (HUTAM) as a mask. The optimal etching conditions for fabricating the diamond stamp were discussed in order to realize a vertical nanopore structure, avoiding structural damage from lateral etching. By using this diamond stamp, a polymer film with the desired hierarchical nanorod array structure can be obtained easily via the simple stamping process, which greatly simplifies the processing procedure. More importantly, the stamp is reusable because of its super-hardness, which ensures the reproducibility of the nanorod array pattern. Another merit is that the smooth surface of the etched diamond can avoid the use of a release agent. Our results prove that this hard stamp can be used for quick preparation of an elaborate periodic nanoarray structure. This study is significant in that it solves the problems of high cost and easy damage of stamps in nanoimprint lithography, and it might inspire more sophisticated applications of such an ordered structure in nanoplasmonics, biochemical sensing and nanophotonic devices.